Optimalisasi Perilaku Hidup Bersih Sehat pada Balita dan Remaja Kelompok Gereja Jawa Di Dusun Trenceng, Desa Mrican, Kabupaten Ponorogo - Pratiwi Hermiyanti; Fitri Rokhmalia; Nuning Marina Pengge; Mujayanto .; Ferry Kriswandana; Demes Nurmayanti; Sri Anggraeni; Nurul Hindaryani; Lembunai Tat Alberta; Endang Soelistyowati; Sri Hardi Wuryaningsih; Sjamsul Arifin (Damhil: Jurnal Pengabdian kepada Masyarakat, 2026)
Clean and Healthy Living Behavior is a promotive-preventive strategy in improving the degree of public health, especially in groups of children and adolescents who are vulnerable to environment-based diseases and nutritional disorders. Church on Trenceng, Mrican Village, Ponorogo Regency, has experienced the chikungunya in 2024, which shows the need to strengthen PHBS practices at the household and church community levels. The purpose of community service is to increase the knowledge of children and adolescents on the implementation of PHBS in the domestic order. Community service is carried out with a participatory educational approach through counseling using flyer media and simple demonstrations. The target was 33 children and adolescents. Health checks are carried out through measurements of height, weight, upper arm circumference, and head circumference to determine nutritional status based on body mass index. The majority of the target had good nutritional status (81.8%), with 9.1% being obese, 6.1% over-nutritional, and 3.0% under-nutrition. Interactive education increases understanding of PHBS practices, including washing hands with soap, consuming balanced nutrition, physical activity, and eradicating mosquito nests. Active participation shows an increase in health awareness in children and adolescents as agents of change in the family.